HM-DyadCap – capture and mapping of 5-hydroxymethylcytosine/5-methylcytosine CpG dyads in mammalian DNA - Engelhard, Lena; Schiller, Damian; Zambrano-Mila, Marlon S.; Keliuotyte, Kotryna; Buchmuller, Benjamin; Tiwari, Shashank; Imig, Jochen; Simeone, Angela; Schröter, Christian; Becker, Sidney; Summerer, Daniel (Technische Universität Dortmund, 2026)
5-Methylcytosine (mC) and 5-hydroxymethylcytosine (hmC) are the main epigenetic modifications of mammalian DNA, and play crucial roles in cell differentiation, development, and tumorigenesis. Both modifications co-exist with unmodified cytosine in palindromic CpG dyads in different symmetric and asymmetric combinations across the two DNA strands, each having unique regulatory potential. To facilitate investigating the individual functions of such dyad modifications, we report HM-DyadCap. This method employs an evolved methyl-CpG-binding domain (MECP2 HM) for the direct capture and sequencing of DNA fragments containing the CpG dyad hmC/mC. Binding studies reveal a high discrimination of MECP2 HM against off-target dinucleotides. We conduct comparative mapping experiments for mESC genomes with HM-DyadCap, standard MethylCap employing wild-type MECP2, as well as MeDIP and hMeDIP protocols. We find that MECP2 HM is blocked by hmC glucosylation and conduct control enrichments with glucosylated genomes that indicate highly selective enrichment of hmC/mC dyads by MECP2 HM. Metagene profiles correlate hmC/mC marks with actively transcribed genes and reveal global enrichment in gene bodies as well as depletion at transcription start sites. We anticipate that HM-DyadCap will enable effective enrichment and mapping of hmC/mC marks with broad applicability for unraveling the function of this dyad in chromatin biology and cancer.
Nucleic acids research; 54(8)
Keywords: 540